Insect Antifeedant Active Substituted Styryl 4-Ethoxyphenyl Ketones - Nalini, S.; Sekar, K. G.; Srinivasan, S.; Muthuvel, I.; Thirunarayanan, G. (Journal of Scientific Research, 2023)
About eleven substituted styryl 4-ethoxy phenyl ketones were synthesized by ultrasound-promoted greener solvent assisted Crossed Aldol condensation of 4-ethoxy acetophenone and various substituted benzaldehydes. In this method, the obtained yield was more than 85 %. These unsaturated ketones were characterized by their analytical and spectroscopic data. The insect antifeedant activity of these ketones was evaluated by castor leaf discs with the 4th instar larvae Achoea Janata L. All enones showed weak, moderate, and good insect antifeedant activity.